Truncated-Exponential-Based General-Appell Polynomials - Ozat, Zeynep; Cekim, Bayram; Ozarslan, Mehmet Ali; Costabile, Francesco Aldo (Mdpi, 2025)
In this paper, a new and general form of truncated-exponential-based general-Appell polynomials is introduced using the two-variable general-Appell polynomials. For this new polynomial family, we present an explicit representation, recurrence relation, shift operators, differential equation, determinant representation, and some other properties. Finally, two special cases of this family, truncated-exponential-based Hermite-type and truncated-exponential-based Laguerre-Frobenius Euler polynomials, are introduced and their corresponding properties are obtained.
Keywords: Appell polynomials; bivariate Appell polynomials; truncated exponential polynomials